The Prosodic Structure Of The Arabic Poem And Its Transformations With Quintuplet And Strophic Poetry As Examples/ البنية العروضية للقصيدة العربية وتحولاتها التخميس والموشحات أنموذجاً - Rahma Moayad Hammodat; Muhammad Ghanem Sharif (Ijaz Arabi Journal of Arabic Learning, 2026)
Prosody is considered as one of the most stable branches of Arabic studies throughout history, as far as it has maintained its principles and rules since its inception. No fundamental changes occurred until approximately the fifth century AH, as the Khalilite meter remained the primary reference in evaluating poetry and judging the soundness of its rhythmic structure. The discovery of this science is attributed to Al-Khalil ibn Ahmad al-Farahidi, who was able to uncover the system behind poetic meters, thus transforming the rhythm from a matter of taste into a science based on precise rules. This established a critical tradition based on adherence to the meters and metrical patterns he had determined. This stability has been reflected in the structure of the Arabic poem, which largely adhered to the established metrical rules. Therefore, the meter became the distinguishing criterion between poetry and other forms of speech, and any deviation from it became a point of concern for critics and prosodists. As a result, any change in the system of meter or rhyme has been noticed as a departure from the inherited poetic balance, not merely a formal variation, because the classical poem is based in its essence on the unity of meter and the regularity of rhythm. In light of this perception, some poetic arts emerged which represented attempts to expand the metrical system without completely separating from it, most notably the quintets and the Strophic Poetry. The study of these two art forms revealed a poetic awareness that sought renewal within the framework of tradition, as the Quintuplet (a type of quintain) preserved the original meter while adding a structural element. Whereas, the Strophic Poetry moved towards greater rhythmic flexibility in response to the demands of singing and composition. Therefore, dealing with these forms is not limited to describing them as newly created arts, but goes beyond that to understand them as manifestations indicative of what can be called prosodic departure, which tests the limits of the rule without abolishing its reference.